BREAST MILK THAT WE DID NOT KNOW: CHRONOBIOLOGY OF BREAST MILK - Sergey E. Ukraintsev; Tatyana N. Samal (Вопросы современной педиатрии, 2018)
The article analyzes modern scientific data on the changes in breast milk composition during lactation. These changes affect both short-term (sleep, appetite) and long-term parameters (growth and development, temperament, behavior) with respect to the health of the child. This information will help to have a better idea of the benefits of breast milk and breastfeeding for a child and to strengthen a support and promotion of breastfeeding among mothers and health workers.